A case report of a MODY6 patient coexistence with Charcot-Marie-Toothe 1A syndrome - Wang, Jianyu; Wang, Chunhua; Chen, Yujie; Qi, Shuang; Wang, Min (Frontiers in Endocrinology, 2025)
Monogenic diabetes, which encompasses neonatal diabetes (NDM), maturity onset diabetes of the young (MODY), and several diabetes-associated syndromes, primarily arises from impaired function or abnormal development of the islets of Langerhans, particularly pancreatic β-cells responsible for insulin secretion. This condition is typically associated with a single pathogenic genetic mutation. Charcot-Marie-Tooth disease type 1A (CMT1A) is a hereditary demyelinating neuropathy that is caused by a duplication of the PMP22 gene located on chromosome 17. Herein, we report a case of a young Chinese patient with MODY6 harboring a novel mutation (c. 317C>T, p. Ala106Val) in the NEUROD1 gene. Additionally, this patient concurrently presents with CMT1A, which is characterized by a large segmental duplication within the exon of the PMP22 gene and its adjacent regions. Considering the patient’s compromised islet function, we treat him with insulin and oral hypoglycemic agents (metformin, acarbose). This represents the first reported instance of a patient with NEUROD1-MODY coexisting with CMT1A.